2020
DOI: 10.5194/nhess-20-2547-2020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the physical vulnerability of buildings affected by slow-moving landslides

Abstract: Abstract. Physical vulnerability is a challenging and fundamental issue in landslide risk assessment. Previous studies mostly focus on generalized vulnerability assessment from landslides or other types of slope failures, such as debris flow and rockfall, while the long-term damage induced by slow-moving landslides is usually ignored. In this study, a method was proposed to construct physical vulnerability curves for masonry buildings by taking the Manjiapo landslide as an example. The landslide's force acting… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Vulnerability refers to the degree of destruction or damage that occurs to one or more affected objects under a specific geohazard intensity [36]. Thus, vulnerability evaluation can help to quantify the relationship between geological disasters and the hazard-bearing body.…”
Section: Vulnerability Evaluation Methodsmentioning
confidence: 99%
“…Vulnerability refers to the degree of destruction or damage that occurs to one or more affected objects under a specific geohazard intensity [36]. Thus, vulnerability evaluation can help to quantify the relationship between geological disasters and the hazard-bearing body.…”
Section: Vulnerability Evaluation Methodsmentioning
confidence: 99%
“…As regards the landslide hazard assessment, a detailed susceptibility analysis could also be applied in risk analysis and integrated with social vulnerability [72,73]. In this context, physical vulnerability, related to the structural features of buildings and infrastructures, such as construction age, material, and the state maintenance of buildings, could be introduced as a development tool for landslide management strategies [74][75][76].…”
Section: Limitations and Suggestionsmentioning
confidence: 99%
“…Landslides are mass movements of rock and soil down a slope, which can be destructive to people and infrastructure causing direct and indirect damage to natural ecosystems (Cruden and Varnes 1996;Geertsema et al 2006;Fell et al 2008a;Geertsema and Foord 2014;Chen et al 2020b;Liang et al 2022). An investigation from the past two decades (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017) has shown that up to 4.8 million people have been affected by landslides, and over 18 thousand people have lost their lives (CRED 2018).…”
Section: Introductionmentioning
confidence: 99%